Viability test on Hevea seeds by the Tetrazolium method - Mohamad Husin, Sakhibun; Chin, H. F.; Hor, Y. L. (Rubber Research Institute of Malaysia, 1981)
The tetrazolium test as a rapid method of estimating the viability of Hevea seeds was investigated. Preliminary studies were to determine the practical preconditioning time and to investigate the optimal concentration, duration and temperature for staining. Seeds imbibed for 4h prior to staining resulted in light and irregular stain, while with longer preconditioning for 16h, the seeds were better stained. Seeds immersed in 1% 2,3,5-triphenyl tetrazolium chloride at 40°C for 2h gave the best uniform red staining of the embryo and endosperm. Using this staining technique, it was found that the results of the tetrazolium test closely correlated with those of the germination test for different quality seeds. The result of the tetrazolium test was obtained in 24h compared to the normal germination test of at least three weeks